Património e Projecto. Uma Casa no Amial. - Maria Ramos Albuquerque (2011)
It has been proposed to us, by a relative who happens to be an architect, to survey that particular house with a discrete appearance, in the Amial area of the city of Porto. The reconversion project should follow, developed by an architect's office and not just by a mere trainee. At a first glance, these two circumstances seemed subject perhaps too low to be considered as part of a master's thesis in architecture. However, seemingly urgent questions were arising. These questions were shared with the architects responsible for the project, throughout this first experience outside the university environment, resulting in a short internship. Some of these questions stimulated our curiosity, deserving further research and consideration and contributing to the arise of new questions. How to intervene in a modern and anonymous heritage that is not properly recognised and classified but that turns out to be an important architectural example? It became important on the very day it was considered the subject of a FAUP's architecture master's degree dissertation. Our first concern about this issue was to understand the scope and importance of this kind of heritage, and reflect how to intervene in face of this new project's situation. How should the architect act before any intervention? What are the consequences of his attitude on the transformation of a building and the city's identity? As far as the architectural project is concerned, we faced several stages of its elaboration and evolution at a pre-existence level. The surveying of the building has been crucial for this new project. Findings supported on this new project have been made. We have recognised, analysed and studied a place, a program and an institutional heritage concerning a religious order - our Client. The final concern was to apply our education in architecture to get the answers in order to achieve the best way to successfully reconvert an old house into a new one without taking away its identity.